2011
DOI: 10.1007/s11136-011-9918-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder, depression, and health-related quality of life in OEF/OIF veterans

Abstract: Findings suggest PTSD and depression contribute uniquely to the negative relationship with HRQoL, adding to the growing literature on distinctive and common effects of these disorders in OEF/OIF veterans. Results highlight the need to better understand the implications for assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 27 publications
8
55
0
1
Order By: Relevance
“…Preventing posttraumatic stress disorder (PTSD) is a priority for military healthcare providers because of its adverse effects on health and financial costs [1][2][3][4][5][6][7][8][9]. For patients with serious combat limb injuries, PTSD can complicate and prolong rehabilitation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventing posttraumatic stress disorder (PTSD) is a priority for military healthcare providers because of its adverse effects on health and financial costs [1][2][3][4][5][6][7][8][9]. For patients with serious combat limb injuries, PTSD can complicate and prolong rehabilitation [8].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with serious combat limb injuries, PTSD can complicate and prolong rehabilitation [8]. PTSD is associated with more sick call visits, missed workdays, increased somatic symptoms [3], poor quality of life outcomes [5], and healthcare costs over $1 billion during the first 2 yr after combat injury [7,9]. Although amputations are among the most serious battle injuries, combat amputees injured in the Iraq and Afghanistan wars had reduced likelihood of PTSD compared with limb salvage patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research indicates that veterans may experience mental health difficulties for as long as 12 years after leaving the Armed Forces (AF) before they seek professional help (Murphy, 2016). Untreated mental health difficulties can be detrimental to veterans’ mental and physical health (Kessler, 2000; Schnurr & Green, 2004), quality of life (Pittman, Goldsmith, Lemmer, Kilmer, & Baker, 2012) and relationships (Shalev, 1997). …”
mentioning
confidence: 99%
“…Depressive disorders and subsyndromal symptomatology may lower one's capacity to enjoy and positively evaluate quality of life. In a sample of veterans, Pittman, Goldsmith, Lemmer, Kilmer, and Baker (2012) found that depression was a significant predictor of psychological but not physical HRQOL. Transgender older adults have been found to have higher depressive symptomatology (FredriksenGoldsen et al, 2013) and lower mental health quality of life (Fredriksen-Goldsen, Kim, Shiu, Goldsen, & Emlet, 2015), than their nontransgender lesbian, gay, and bisexual counterparts, who themselves experience significantly poorer mental health than their heterosexual age peers (Fredriksen-Goldsen, Kim, Barkan, Muraco, & Hoy-Ellis, 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 96%